تأثير المعالجات الحرارية للفولاذ على انتشار شقوق التعب - سليمان علي (Tishreen University, 2018)
This article aims to calculate the number of loading cycles required to   fatigue crack propagation and to study the influence of heat treatment (carburizing, nitriding and Case-hardening) on the fatigue crack propagation period. For this propose and using Matlab, the period of crack propagation has modeled using the stress intensity factors and the diameter of plastic deformation zone generated at crack tip depending on Paris law. The obtained results show the positive role of residuals stresses resulted from heat treatment in reduce the long of crack and in increase the life period of bodies subjected to the contact fatigue. يهدف هذا البحث إلى حساب عدد دورات التحميل اللازمة لانتشار شقوق التعب بين سطوح الأجسام المتماسة, ودراسة تأثير نوع المعالجة الحرارية (كربنة , نترجة وتقسية سطحية) على زمن انتشار الشقوق. لأجل هذا الغرض وباستخدام لغة الماتلاب تم نمذجة زمن انتشار الشقوق بالاعتماد على قيمة عوامل كثافة الإجهادات وقطر منطقة التشوه اللدن (البلاستيكي) المتكونة في قمة الشق وذلك باستخدام قانون باريس لحساب عدد دورات التحميل اللازمة لانتشار شقوق التعب.  تشير النتائج الحاصلة إلى الدور الايجابي الذي تلعبه الإجهادات المتبقية والناتجة عن المعالجات الحرارية من حيث زيادة عدد دورات التحميل اللازمة لانتشار شق التعب من جهة, وإنقاص طول الشق المتكون نتيجة للتعب من جهة أخرى.